MicroRNA-18 facilitates the stemness of gastric cancer by downregulating HMGB3 though targeting Meis2. Issue 4 (1st April 2022) - Zhang, Yingjun; Lin, Weijian; Jiang, Weiping; Wang, Zhenfa
ABSTRACT: The recurrence and metastasis of gastric cancer are related to the stemness of gastric cancer cells. Researches have shown that miR-18 level is negatively correlated to the occurrence and development of certain cancer types. However, the effects of miR-18 on the stemness of gastric cancer remain uncertain. In this research, gastric cancer cell lines with stable overexpression of miR-18 were constructed through lentivirus infection. CCK-8 assay, RT-qPCR, Western blot, flow cytometry, and in vivo tumorigenesis assays were performed to evaluate the effects of miR-18 on the stemness of gastric cancer cells. Moreover, luciferase reporter assays found that Meis2 was the target of miR-18. Furthermore, we also found that the low-expressed oncogene HMGB3 is involved in this miR-18/Meis2 axis to further promote the stemness of gastric cancer cells. These findings suggest that the miR-18/Meis2/HMGB3 axis may be potential prognostic indicators for patients with gastric cancer. Graphical Abstract: uf0001